Responsive mechanism and molecular design of di-2-picolylamine-based two-photon fluorescent probes for zinc ions - 朱美玉;赵珂;宋军;王传奎 (Chinese physics B, 2018)
The properties of one-photon absorption（OPA）, emission and two-photon absorption（TPA） of a di-2-picolylaminebased zinc ion sensor are investigated by employing the density functional theory in combination with response functions.The responsive mechanism is explored. It is found that the calculated OPA and TPA properties are quite consistent with experimental data. Because the intra-molecular charge transfer（ICT） increases upon zinc ion binding, the TPA intensity is enhanced dramatically. According to the model sensor, we design a series of zinc ion probes which differ by conjugation center, acceptor and donor moieties. The properties of OPA, emission and TPA of the designed molecules are calculated at the same computational level. Our results demonstrate that the OPA and emission wavelengths of the designed probes have large red-shifts after zinc ions have been bound. Comparing with the model sensor, the TPA intensities of the designed probes are enhanced significantly and the absorption positions are red-shifted to longer wavelength range. Furthermore, the TPA intensity can be improved greatly upon zinc ion binding due to the increased ICT mechanism. These compounds are potential excellent candidates for two-photon fluorescent zinc ion probes.